Phyto-Constituents of Two Medicinal Plant Species Used as Aphrodisiacs in Ghana - Ameyaw, Y.; Barku, V.Y.A.; Bashiru, Fatawu (Asian Journal of Chemistry, 2010)
Two aphrodisiac plant species; Mondia whitei and Hallea stipulosa originally called Mitragyna stipulosa were collected from Begoro in the Fanteakwa District in the Eastern Region of Ghana for the research. The dried stem-barks of the two plant species were extracted with methanol and ethanol. The extracts (crude drugs) were screened for alkaloids, steroids, tannins, coumarins and reducing sugars. With the exception of tannins, the other four compounds were positively present in the plant species.